Development of Tourism Village Through Community-Based Tourism (CBT) Concept Approach in Branjang Village (Indonesian Journal of Devotion and Empowerment, 2022)
This service activity aims to understand the development of tourist villages and awareness of village community participation. The service method used is socialization and training. The target audience for the service activities is the village government and POKDARWIS Branjang Village. Activities are packaged in the form of webinars and discussions using zoom meetings. The results show that the village government, POKDARWIS managers, and the community can understand the concept of developing a tourist village and its mapping for community welfare. Branjang Village has officially become a Tourism Village based on the decision of the Central Java Provincial Tourism Office. Community involvement in determining tourism potential and opportunities is the primary key to developing a tourist village. In addition, the Village's understanding of community-based tourism continues to be socialized through POKDARWIS, which is ready with its vision and mission to develop tourism in the Village. Funding and policy support continues to be carried out so that tourism in the Village can continue to exist and benefit the broader community. Tujuan kegiatan pengabdian ini adalah pemahaman pengembangan desa wisata dan kesadaran partisipasi masyarakat desa. Metode pengabdian yang digunakan adalah sosialisasi dan pelatihan. Khalayak sasaran kegiatan pengabdian adalah pemerintah desa dan POKDARWIS Desa Branjang. Kegiatan dikemas dalam bentuk webinar dan diskusi menggunakan zoom meeting. Hasil menunjukkan bahwa pemerintah desa, pengelola POKDARWIS, serta masyarakat dapat memahami konsep pengembangan desa wisata dan pemetaanya untuk kesejahteraan masyarakat. Saat ini Desa Branjang telah resmi menjadi Desa Wisata berdasarkan keputusan Dinas Pariwisata Provinsi Jawa Tengah. Keterlibatan masyarakat dalam menentukan potensi wisata dan peluang wisata menjadi kunci utama keberhasilan pengembangan desa wisata. Disamping itu, pemahaman tentang pariwisata berbasis masyarakat terus disosialisasikan oleh Desa melalui POKDARWIS yang siap dengan visi misinya mengembangkan wisata yang ada di desa. Dukungan dana dan kebijakan terus dilakukan agar wisata yang ada di desa dapat terus eksis dan memberikan manfaat bagi masyarakat luas.